The Expression and Clinical Significance of PA28 γ in Colorectal Cancer. (December 2013) - Chen, Debo; Yang, Xiaosong; Huang, Liyong; Chi, Pan
Objective: The aims of this study were to detect differences in PA28 γ expression between healthy colorectal, colorectal adenoma, and colorectal cancer (CRC) tissues and to explore the significance of PA28 γ in the development of CRC. Methods: Western blotting was used to assay the PA28 γ expression protein in the healthy colorectal and the CRC tissue. Tissue array was used to assay the PA28 γ expression in the healthy colorectal, colorectal adenoma, and CRC tissues. Follow-up was performed in the patients with CRC, and survival analysis was used to assay the correlation between PA28 γ and the survival time after surgical resections. Results: The Western blotting results revealed that the PA28 γ expression was higher in the CRC tissue than in the healthy colorectum. Tissue array showed that PA28 γ was low in the healthy colorectum, higher in the colorectal adenoma, and highest in the CRC tissue. The expression of PA28 γ correlated with differentiation and TNM stage of the CRC tissue. However, there was no significant difference in the PA28 γ expression between CRC and rectal cancer. No significant difference was found in survival rate between PA28 positive staining and PA28 negative staining. The Cox proportional hazard model showed that the survival time correlated with only the differentiation degree of CRC. Conclusions: PA28 γ was involved in the early events of CRC. It contributes to the carcinogenesis and progression of CRC and may be a biomarker for the early diagnosis of CRC.